Field Observations During the Fourth Microwave Water and Energy Balance Experiment (MicroWEX-4): from March 10 - June 14, 2005 - Joaquin Casanova; Tzu-yun Lin; Mi-young Jang; Kai-Jen Calvin Tien; Jasmeet Judge; Orlando Lanni; Larry Miller (EDIS)
The goal of MicroWEX-4 was to understand the land-atmosphere interactions during the growing season of corn, and their effect on observed microwave brightness signatures at 6.7 GHz, matching that of the satellite based microwave radiometer, AMSR. This document is Circular 1482, one of a series of the Department of Agricultural and Biological Engineering, UF/IFAS Extension. Original publication date November 2005.